소방대원 개인보호용 전자장비 패키징 기술개발 - 박우태; 이상엽; 전지원; 최한탁; 우희권; 우덕하 (한국센서학회, 2015)
While the conventional personal protective equipments (PPEs) covers a variety of devices and garments such as respirators, turnout gear, gloves, blankets and gas masks, several electronic devices such as personal alert safety system (PASS) and heads-up displays in the facepiece have become a part of firefighters personal protective equipments through past several years. Furthermore, more advanced electronic sensors including location traking sensor, thermal imaging caerma, toxic gas detectors, and even physiological monitoring sensors are being integrated into ensemble elements for better protection of firefighters from fire sites. Despite any electronic equipment placed on the firefighter must withstand environmental extremes and continue to properly function under any thermal conditions that firefighters routinely face, there are no specific criteria for these electronics to define functionability of these devices under given thermal conditions. Although manufacturers provide the specifications and performance guidelines for their products, their operation guidelines hardly match the real thermal conditions. Present study overviews firefighter’s fatalities and thermal conditions that firefighters and their equipments face. Lastly, thermal packaging methods that we have developed and tested are introduced.